Study of shelter management of cattle under field conditions in and around greater Guwahati of Assam (Indian Journal of Animal Production and Management, 2024)
The study was under taken for assessment of shelter management of dairy cows in and around the greater  Guwahati city of Assam. Total 173 numbers of farmers were randomly selected from the specified areas  and divided into two categories viz. farmers having crossbred cattle (F1) and farmers with only local cattle  (F2). The crossbred cattle were reared in intensive and local cattle were in semi-intensive system of feeding.  The long axis of sheds was 35.84, 26.59, 23.70 and 13.87 percent in the north-south, east-west, north-west  and south-west orientations, respectively. Thatched roofs were 75.72 percent followed by 19.65 and 4.62  percent corrugated G.I. and asbestos sheeted, respectively. There was highly significant (p
Keywords: Cattle; Field condition; Management; Shelter